Best Practice Manajemen Ekstrakurikuler Literasi Anak dalam Meningkatkan Minat Belajar Anak Usia Dini - Syakuro, Moh. Abdan (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2023)
The decrease in children's learning interest is a problem that occurs within early childhood, thereby disrupting the learning comfort in school. This research aims to describe the best practices of children's literacy extracurricular management in enhancing the learning interest of early childhood. The research method employed is qualitative descriptive with a case study approach. The research subjects consist of four tutoring teachers, the head of the tutoring center, and seven tutoring participants aged 3-6 years. The data collection for this research utilizes interview, observation, and documentation methods. The research technique employs source triangulation and method triangulation. The results of this research indicate that the tutoring activities at Les Privat Kedatim provide significant benefits to the development of early childhood. Through tutoring, children enhance their learning motivation, acquire better repetition and understanding of teaching materials, and develop problem-solving skills. The comprehensive teaching materials cover all subjects taught in school and are delivered through various activities. The management of tutoring centers also plays a crucial role in the success of this program. Government support in the form of funding and facilities needs to be considered to enhance the institutionalization and sustainability of this program. Overall, tutoring at Les Privat Kedatim has a significant positive impact on learning motivation and early childhood development.